A Fire-Retardant Composite Made from Domestic Waste and PVA. (27th June 2016) - Surtiyeni, Neni; Rahmadani, Raidha; Kurniasih, Neny; Khairurrijal,; Abdullah, Mikrajuddin
Abstract : We report the synthesis of a composite from domestic waste with the strength of wood building materials. We used original domestic waste with only a simple pretreatment to reduce the processing cost. The wastes were composed of organic components (generally originating from foods), paper, plastics, and clothes; the average fraction of each type of waste mirrored the corresponding fractions of wastes in the city of Bandung, Indonesia. An initial survey of ten landfills scattered through Bandung was conducted to determine the average fraction of each component in the waste. The composite was made using a hot press. A large number of synthesis parameters were tested to determine the optimum ones. The measured mechanical strength of the produced composite approached the mechanical properties of wood building materials. A fire-retardant powder was added to retard fire so that the composite could be useful for the construction of residential homes of lower-income people who often have problems with fire. Fire tests showed that the composites were more resistant to fire than widely used wood building materials.